2013
DOI: 10.1007/s00521-013-1490-z
|View full text |Cite
|
Sign up to set email alerts
|

Predicting phishing websites based on self-structuring neural network

Abstract: -Internet has become an essential component of our everyday social and financial activities. Nevertheless, internet-users may be vulnerable to different types of web-threats which may cause financial damages, identity theft, loss of private information, brand reputation damage and loss of customer's confidence in ecommerce and online banking. Phishing is considered as a form of web-threats that is defined as the art of impersonating a website of an honest enterprise aiming to obtain confidential information su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
167
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(173 citation statements)
references
References 23 publications
0
167
0
6
Order By: Relevance
“…In this research, we list 16 frequently used features in literatures [8], [21], [23]- [25] and one new feature, and make use of them to perform feature engineering.…”
Section: Feature Vectormentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, we list 16 frequently used features in literatures [8], [21], [23]- [25] and one new feature, and make use of them to perform feature engineering.…”
Section: Feature Vectormentioning
confidence: 99%
“…-IP address ( f 1 ): almost all the literatures [8], [21], [23]- [25] [24], [25] followed and used this rule to define the value of this feature. However, this rule was highly affected by the samples.…”
Section: Feature Vectormentioning
confidence: 99%
“…The success of phishing website detection techniques mainly depends on recognizing phishing websites accurately and within an acceptable timescale [2], [4]. Many conventional techniques based on fixed black and white listing databases have been suggested to detect phishing websites.…”
Section: Introductionmentioning
confidence: 99%
“…Mohammad et al [9] suggested rule-based data mining classification techniques with 17 different features to distinguish phishing from legitimate websites. Mohammad et al [4] proposed an intelligent model for predicting phishing attacks based on self-structuring neural networks. Abdelhamid et al [1] developed an approach called Multi-Label Classifier based Associative Classification (MCAC) to detect phishing websites.…”
Section: Introductionmentioning
confidence: 99%
“…Common applications of classification are medical diagnoses (RameshKumar et al, 2013), phishing detection , fraud detection (Whitten and Frank, 2005), etc. Some of the main classification approaches developed in data mining include Decision Trees (DT) (Quinlan, 1993), Neural Network (NN) (Mohammad et al, 2013), Associative Classification (AC) (Thabtah, et al, 2004) (Thabtah, 2005), and Rule Induction (RI) (Cendrowska, 1987). The latter two approaches extract classifiers that contain human interpretable rules in the form "If-Then", which explain their wide spread applicability.…”
Section: Introductionmentioning
confidence: 99%